2023
DOI: 10.3390/plants12101973
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthus Biochar-Based Microbial Cell Composites for Alleviation of Drought and Cadmium Stress: A Novel Bioremediation Approach

Abstract: Metal contamination coupled with aridity is a major challenge for remediation of abiotic stressed soils throughout the world. Both biochar and beneficial bacteria showed a significant effect in bioremediation; however, their conjugate study needs more exploration. Two rhizobacteria strains Serratia sp. FV34b and Pseudomonas sp. ASe42b isolated from multi-metal and drought stressed sites showed multiple plant-growth-promoting attributes (phosphate solubilization, indole-3-acetic acid, siderophore, and ammonia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…However, the accumulation of proline under HM, drought, and HM+drought stress conditions was significantly lower in ARN7- and GS-BC-treated plants compared to their respective control counterparts ( Figure 3 b). Similar observations were previously documented by Anbuganesan et al [ 7 ] and Tripti et al [ 16 ] where they noted reduced proline content upon the application of biochar and PGP bacteria under HM and drought stress conditions and suggested that treatment with biochar and PGP bacteria cumulatively reduced the stress effects caused by HM and drought.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the accumulation of proline under HM, drought, and HM+drought stress conditions was significantly lower in ARN7- and GS-BC-treated plants compared to their respective control counterparts ( Figure 3 b). Similar observations were previously documented by Anbuganesan et al [ 7 ] and Tripti et al [ 16 ] where they noted reduced proline content upon the application of biochar and PGP bacteria under HM and drought stress conditions and suggested that treatment with biochar and PGP bacteria cumulatively reduced the stress effects caused by HM and drought.…”
Section: Resultssupporting
confidence: 90%
“…Recently, bioaugmentation with plant growth-promoting rhizobacteria (PGPR) has also gained great attention as an effective strategy to mitigate various abiotic stresses in plants and improve crop productivity [ 16 , 17 , 18 ]. PGPR with the potential to tolerate abiotic stresses including HM, drought, etc., can colonize the plant rhizosphere and exhibit beneficial effects on plants by synthesizing various plant growth-promoting (PGP) substances such as 1-aminocyclopropane-1-carboxylate deaminase, siderophores, indole-3-acetic acid (IAA), exopolysaccharides, antimicrobial metabolites, N fixation, and solubilizing P, K, Zn, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, soil-associated stressors such as water scarcity and heavy metals may be more detrimental in terms of plant morphological, physiological, and biochemical processes, which could lead to decrement in growth, biomass, and yield. Known as a highly toxic heavy metal, cadmium (Cd) is released into the environment through human activities such as mining, fertilizers, pesticides, and industrial processes (Tripti et al, 2023). Plants easily accumulate Cd from the soil, and excessive Cd uptake leads to metabolic defects and growth inhibition (Zhang et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%